PENGEMBANGAN SKILL DAN KOMPETENSI TIK GURU MATEMATIKA DAN IPA KOTA JAMBI MELALUI e-TUTORIAL BERBASIS KEBUTUHAN GURU(TEACHER’S NEED) - Marzal, Jefri (Program Magister Teknologi Pendidikan Universitas Jambi, 2013)
To improve the quality of learning, the government has attempted to facilitate school with equipment Information and Communication Technology (ICT), such as the procurement of computer labs, school computer connection to the Internet, and increase the skills of teachers in computer operationalize. In fact, only a few teachers who use computers for a whole series of teaching, starting from the use of computers to plan instruction, learning activities and evaluation of learning. The research reveals the teacher's perception of the skills and knowledge, and determine the factors that influence the control of teachers in ICT. Furthermore, this study also develops a tutorial www.etiktutor.org website dedicated to teachers who want to improve their knowledge and ICT skills through online tutorials. The survey results in this study show turns the ability of ICT teachers are categorized Jambi, and the factors that most influence on teachers' ICT capability is the availability of ICT tools and teacher access to participate in ICT education. Furthermore, the website tutorial tutorial materials based on the needs of teachers has received a very positive perception of teachers, where they say that www.etiktutor.org website is very useful to improve the knowledge and ability of mathematics teacher ICT and science high school in the city of Jambi. Keyword: communication technology competence, e-tutorial